2017
DOI: 10.1111/cpr.12404
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs in rheumatoid arthritis

Abstract: Rheumatoid arthritis, a disabling autoimmune disease, is associated with altered gene expression in circulating immune cells and synovial tissues. Accumulating evidence has suggested that long non-coding RNAs (lncRNAs), which modulate gene expression through multiple mechanisms, are important molecules involved in immune and inflammatory pathways. Importantly, many studies have reported that lncRNAs can be utilized as biomarkers for disease diagnosis and prognostication. Recently, dysregulation of lncRNAs in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Previous researchers have identified differentially expressed lncRNAs in PBMCs and synovial fibroblasts in patients with RA, a chronic inflammatory joint disease [ 29 , 30 , 31 , 32 ]. While the functions of most of these lncRNAs remains unknown, Hotair has been reported to enhance the migration of activated macrophages, thereby participating in RA pathogenesis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have identified differentially expressed lncRNAs in PBMCs and synovial fibroblasts in patients with RA, a chronic inflammatory joint disease [ 29 , 30 , 31 , 32 ]. While the functions of most of these lncRNAs remains unknown, Hotair has been reported to enhance the migration of activated macrophages, thereby participating in RA pathogenesis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that lncRNAs participate in the initiation and progression of several types of bone diseases including bone tumors (27), osteoarthritis (OA) (28,29), osteoporosis (30,31), RA (32) and ankylosing spondylitis (AS) (33). MEG3 has been shown to be involved in the development of the all these bone diseases, as shown in Table II. MEG3 and bone tumors.…”
Section: Roles Of Lncrna Meg3 In Bone Diseasesmentioning
confidence: 95%
“…RNAs with >200 nucleotides in length. [17][18][19] Accumulating evidence suggested that lncRNAs are deregulated in most, if not all, types of human diseases, including tumours, cardiovascular diseases, autoimmune diseases and congenital abnormalities. [20][21][22][23][24] Mechanistically, lncRNAs modulate gene expression at transcriptional and post-transcriptional levels and participate in the regulation of a plethora of molecular, cellular and tissue processes, including DNA synthesis, chromatin modification, cell proliferation, apoptosis, differentiation and organ development.…”
Section: Long Non-coding Rnas (Lncrnas) Are a Group Of Non-codingmentioning
confidence: 99%